LOW SERUM BNP LEVELS IN TYPE II DIABETES MELLITUS - DR.B.SHANTHI,; DR.K.GUNANITHI,; DR.A.J.MANJULA DEVI, (International Journal of Pharma and Bio Sciences, 2013)
BNP, B type natriuretic peptide, an established marker of heart failure, also has a role to play in obesity and diabetes. The phenomenon of natriuretic handicap ( i.e., reduced / impaired natriuretic peptide response is common among type II diabetes mellitus patients.Our aim was to investigate the clinically meaningful associations which implicated low serum BNP levels with obese type II diabetes mellitus patients.The association between low BNP levels and diabetes in the study population supports the phenomenon of natriuretic handicap and so its predisposition to hypertension and other cardiovascular disorders and thereby BNP levels can be assessed as a routine in obese diabetics to assess their status of natriuretic response.